Reducing Pending BPJS Claims Through Risk Management: Mengurangi Klaim BPJS yang Tertunda Melalui Manajemen Risiko - Fitri Hariyanti; Cholifah Cholifah (Academia Open, 2024)
Pending BPJS claims delay hospital payments, with the guarantee unit playing a crucial role. This study analyzes risk management in the guarantee unit regarding pending inpatient claims using a qualitative approach and the FMEA method. Data from interviews, questionnaires, and BPJS claim confirmation sheets revealed four potential risks causing pending claims, with readmission potential as the highest priority (RPN score of 75). The proposed improvements include coordinating, socializing, and educating related units on the readmission concept. Implementing these strategies can reduce pending claims, ensuring timely BPJS payments to hospitals. Highlight: Identified four risks causing pending claims. Readmission risk prioritized (RPN score 75). Education and coordination proposed to reduce claims. Keyword: BPJS claims, risk management, guarantee unit, FMEA, readmission